Pengetahuan Dan Peran Orang Tua Dalam Penanganan Stunting Pada Anak Di Kecamatan Tuah Madani Kota Pekanbaru - Dika Ankholla; Rina Susanti (Departement of Mathematics Education, 2025)
Knowledge is very important for parents in understanding child development. With knowledge, parents can take appropriate action to avoid the risk of stunting in children. This study uses Hinkel's theory of action to see parental actions. The purpose of this study is to determine the knowledge and efforts of parents in handling child stunting. This type of research is field research with a descriptive quantitative approach that connects the role and knowledge of parents in handling child stunting. The population used is parents in Tuah Madani District who are registered at the Sidomulyo RJ Health Center as parents of stunted children with a total of 34 samples using census techniques on all members of the population. Data collection techniques use questionnaires, observation and documentation. Data analysis The data that has been collected will be calculated through central tendency measurements.with mean, mode, drink value and maximum value. The results of the study found that the fulfillment of consumption has the highest level of parents as an effort to handle stunted children. The causative factors and impacts that occur in stunted children are the highest knowledge understood by parents.